Ductility prediction of HPDC aluminum alloy using a probabilistic ductile fracture model. (June 2022) - Zhang, Yongfa; Shen, Fuhui; Zheng, Jiang; Münstermann, Sebastian; Li, Tianjiao; Han, Weijian; Huang, Shiyao
Highlights: The microstructure and ductile fracture characteristics of the aluminum alloy (Aural-2) produced by high-pressure die casting have been thoroughly characterized via experimental and numerical approaches. Stochastic ductile fracture property observed over a wide range of stress states of the studied material could be captured by the proposed classic ductile damage model in combination with the probabilistic function. Simulation results of 3D synthetic finite element models indicate that the global failure strain and the local crack propagation path can be precisely predicted using the calibrated probabilistic damage mechanics model. Abstract: The microstructure and ductile fracture characteristics of the aluminum alloy (Aural-2) produced by high-pressure die casting have been characterized via experimental and numerical approaches. The stochastic distribution of casting defects (i.e., initial porosity), which is measured by X-ray tomography, leads to a pronounced scatter in the ductile fracture properties of the alloy. Numerical investigations on the ductile fracture behavior have revealed a considerable stress triaxiality dependence of fracture initiation strain, whereas the Lode angle parameter has only marginal effects on the ductile fracture behavior in this material. A probabilistic damage mechanics model is put forward to depict the apparent stochastic ductile fracture behavior over a wide range of stress states. Detailed calibration and validation of model parameters are elaborated in comparison with experimental results. As a further application of the calibrated probabilistic damage mechanics model, the deformation and fracture behavior of heterogeneous structures containing defects has been simulated. Simulation results have confirmed that the variation of initial porosity in different specimens is one of the dominating factors attributed to the observed scatter of failure strain. When the calibrated fracture criteria are applied to simulate the deformation of synthetic porosity-containing finite element models, both the global failure strain and the local crack propagation path can be precisely predicted.